Morningside : the 1979 Greensboro massacre and the struggle for an American city's soul - Shetterly, Aran, 1970- (Amistad, an imprint of HarperCollins Publishers, 2024)
"On November 3, 1979, as activist Nelson Johnson assembled people for a march adjacent to Morningside Homes in Greensboro, North Carolina, gunshots rang out. A caravan of Klansmen and Neo-Nazis sped from the scene, leaving behind five dead. Known as the "Greensboro Massacre," the event and its aftermath encapsulate the racial conflict, economic anxiety, clash of ideologies, and toxic mix of corruption and conspiracy that roiled American democracy then--and threaten it today. In 88 seconds, one Southern city shattered over irreconcilable visions of America's past and future. When the shooters are acquitted in the courts, Reverend Johnson, his wife Joyce, and their allies, at odds with the police and the Greensboro establishment, sought alternative forms of justice. As the Johnsons rebuilt their lives after 1979, they found inspiration in Nelson Mandela's post-apartheid Truth and Reconciliation Commission and Martin Luther King Jr's concept of Beloved Community and insist that only by facing history's hardest truths can healing come to the city they refuse to give up on. This intimate, deeply researched, and heart-stopping account draws upon survivor interviews, court documents, and the files from one of the largest investigations in FBI history. The persistent mysteries of the case touch deep cultural insecurities and contradictions about race and class. A quintessentially American story, Morningside explores the courage required to make change and the evolving pursuit of a more inclusive and equal future." --